On Generalized Absolute Riesz Summability Method - Kartal, Bağdagül (Communications in Mathematics and Applications, 2017)
This paper presents a generalization of a known theorem dealing with absolute Riesz summability of infinite series to the φ-|N,p_n;δ|_k summability.